2014
DOI: 10.1107/s205225251402003x
|View full text |Cite
|
Sign up to set email alerts
|

Viruses and viral proteins

Abstract: For more than 30 years X-ray crystallography has been by far the most powerful approach for determining the structures of viruses and viral proteins at atomic resolution. The information provided by these structures, which covers many important aspects of the viral life cycle such as cell-receptor recognition, viral entry, nucleic acid transfer and genome replication, has extensively enriched our vision of the virus world. Many of the structures available correspond to potential targets for antiviral drugs aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 115 publications
(109 reference statements)
0
18
0
Order By: Relevance
“…Bottlenecks are more probably due to restrictions of the number of infectious viruses that reaches a target tissue or organ than to an insufficient number of receptor molecules on the cell surface. The interaction of a virus with one or several receptors (or a receptor and a coreceptor) will generally allow virus entry, which is a multistep process that involves changes in virion structure, a succession of low-and high-affinity binding to one or more cellular proteins, and membrane fusion in the case of enveloped viruses (Verdaguer et al, 2014;Strauss et al, 2015).…”
Section: Modifications Of Host Cell Tropism and Host Rangementioning
confidence: 99%
“…Bottlenecks are more probably due to restrictions of the number of infectious viruses that reaches a target tissue or organ than to an insufficient number of receptor molecules on the cell surface. The interaction of a virus with one or several receptors (or a receptor and a coreceptor) will generally allow virus entry, which is a multistep process that involves changes in virion structure, a succession of low-and high-affinity binding to one or more cellular proteins, and membrane fusion in the case of enveloped viruses (Verdaguer et al, 2014;Strauss et al, 2015).…”
Section: Modifications Of Host Cell Tropism and Host Rangementioning
confidence: 99%
“…In fish, with purified virus particles used as targets, RNA aptamers with therapeutic potential were generated against viral hemorrhagic septicemia virus and Hirame rhabdovirus (Hwang et al, 2012;Punnarak et al, 2012). In a previous study, we selected a panel of DNA aptamers against purified SGIV particles, and demonstrated their inhibitory effects on viral infection in vitro and in vivo (Li et al, 2014 Verdaguer et al, 2014). Based on these modifications, or other markers of virus-infected cells, highly specific molecular probes could be designed.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular characteristics of cells infected by virus, especially at the proteomic level, are critical in understanding viral pathogenesis and designing targeted therapies (Gerold & Pietschmann, 2014;Karst et al, 2015;Seeger & Mason, 2015;Verdaguer et al, 2014). Our aptamers recognized SGIV-infected cells as early as 8 h p.i., indicating that the targets of Q2, Q3, Q4 and Q5 were apparent at the surface of SGIV-infected cells from 8 h p.i.…”
mentioning
confidence: 95%
“…Bottlenecks are more probably due to restrictions of the number of infectious virus that reaches a target tissue or organ than to insufficient number of receptor molecules on the cell surface. The interaction of a virus with one or several receptors (or a receptor and a coreceptor) will generally allow virus entry which is a multistep process that involves changes in virion structure, a succession of low-and high-affinity binding to one or more cellular proteins, and membrane fusion in the case of enveloped viruses (Verdaguer et al, 2014;Strauss et al, 2015).…”
Section: Modifications Of Host Cell Tropism and Host Rangementioning
confidence: 99%